(untitled) (Indonesian Health Justice Review, 2024)
Child health in Indonesia is marked by significant inequalities, with children from marginalized groups experiencing disproportionate rates of malnutrition, preventable diseases, and inadequate healthcare access. This paper investigates the health disparities faced by Indonesia’s most vulnerable children, focusing on the structural and systemic barriers to quality pediatric care. Through a combination of health data analysis, interviews with healthcare providers, and surveys of families in low-income and rural areas, the study highlights key factors contributing to child health inequities, including poverty, lack of healthcare facilities, and inadequate nutrition. Findings suggest that although national health programs, such as the Healthy Indonesia Program, have improved child health outcomes, significant gaps remain, particularly in rural and indigenous communities. The paper advocates for a child-centered approach to health justice, emphasizing the need for targeted interventions to address social determinants of health, improve immunization rates, and enhance maternal and child healthcare services. Recommendations include increasing investment in pediatric healthcare infrastructure, improving access to nutrition, and expanding health education campaigns for parents and caregivers.